Bitcoin Intelligence - Business Intelligence meets Crypto Currency - Horia Mircea Botos (CES Working Papers, 2017)
Bitcoin is a decentralized digital currency, which works peer-to-peer without a centralized repository, and is accepted as a form of payment all around the world. The “public ledger”, which registers transactions, is known as the block chain. A conventional ledger records bills and notes which are used by an organization, but in the case of Bitcoin these are simply data “entries” in the Blockchain sequence. Business Intelligence (BI), according to Investpedia, refers to the procedural and technical infrastructure that collect, store and analyses the data produced by a field of activities or by an individual company. BI is meant to take in all the data being generated by a business and present easy to digest performance measures and trends that will inform management decisions. The paper shows the BI steps and procedures that will help a Bitcoin user, owner or broker make the best decision possible in order to maximize their profits and financial security.
Keywords: 330; Bitcoin; Business Intelligence; Crypto Currency; Intelligence; Security